2017
DOI: 10.5539/ijel.v7n2p176
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Attitudes towards Educational Technology in English Language Institutes

Abstract: The issue of attitude towards technology is not a new one; it has been around since computers were first placed in the classroom. There appears to be a positive attitude towards technology, so researchers aimed to seek out new information in an effort to find the relationship among teachers' tenure, age, educational level, experience and teachers' attitude toward technology. The purpose of this study was to investigate the attitude towards technology among teachers working in several institutes in Mazandaran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
3
10
2
Order By: Relevance
“…The findings of the study also showed that there is no significant difference between teachers' technology integration regarding their age. This is contrary to some previous studies that argued that there is a significant difference between age and teachers' attitude towards ICT use (Cavas et al, 2009;Seraji et al, 2017). The studies showed that younger teachers' attitude towards computer is more positive and lower computer anxiety than older teachers.…”
Section: Discussioncontrasting
confidence: 75%
“…The findings of the study also showed that there is no significant difference between teachers' technology integration regarding their age. This is contrary to some previous studies that argued that there is a significant difference between age and teachers' attitude towards ICT use (Cavas et al, 2009;Seraji et al, 2017). The studies showed that younger teachers' attitude towards computer is more positive and lower computer anxiety than older teachers.…”
Section: Discussioncontrasting
confidence: 75%
“…The more positive a teacher is about ICT, the more likely it is that they will use the technology. In addition, a study conducted by Seraji et al (2017) revealed that younger teachers were more positive towards ICT use in teaching than were older teachers. Also, the less experienced teachers had a more positive attitude than did the more experienced teachers (Inan & Lowther, 2010).…”
Section: Usage Accessmentioning
confidence: 99%
“…Similar findings have been documented in Zanguyi's [66] study examining educators' attitudes toward the deployment of technology in learning. In another recent study, Seraji et al [67] examined the attitude towards ICT usage amongst teachers originating from various institutions in Mazandaran. The sample involved 62 female and 38 male teachers, and the findings demonstrated that there was a statistically significant correlation between the attitude of teachers and their experience with technology.…”
Section: B Attitudes Towards the Use Of Technologymentioning
confidence: 99%
“…When the teachers have a positive attitude, technology is perceived positively. Moreover, Seraji et al [67] discovered that there was a statistical relationship between the teachers' tenure and age with their attitude towards ICT. That is, younger teachers have a considerably more positive attitude towards the use of technology as compared to older teachers.…”
Section: B Attitudes Towards the Use Of Technologymentioning
confidence: 99%